A Piranha-like pycnodontiform fish from the Late Jurassic - Kölbl-Ebert, Martina; Ebert, Martin; Bellwood, David R.; Schulbert, Christian (Current Biology, 2018)
Pycnodontiformes are an extinct order of ray-finned fishes from the Triassic to Eocene [1, 2], with a characteristic crushing dentition reflecting a highly specialized diet [3]. However, our discovery of a new pycnodontiform from the Late Jurassic (ca. 152 Ma) Plattenkalk deposits of the Solnhofen Archipelago revealed long, pointed teeth along the vomer and triangular teeth with cutting edges along the prearticulars. This is the earliest evidence of specialized flesh cutting in a ray-finned fish. The dentition pattern, tooth shape, jaw morphology, and mechanics are all indicative of a feeding apparatus suitable for slicing flesh or fins, thus pioneering a new ecological niche. Evidence suggests that it may have exploited aggressive mimicry in a striking parallel to the feeding patterns of modern piranha. Remarkably, fossil fishes recovered from the same deposits as the new pycnodontiform show injuries to fins and fin bases. As a marine piranha-like fish contemporary with dinosaurs, it is the oldest known flesh-eating actinopterygian, revealing remarkable convergent evolution with modern piranhas. Kölbl-Ebert et al. describe a new pycnodontiform fish, Piranhamesodon pinnatomus, from the Jurassic. It has specialized morphological features for cutting flesh, including piranha-like teeth. As a marine fish contemporary with dinosaurs, it is the oldest known flesh-eating ray-finned fish, exhibiting remarkable convergent evolution with piranhas.
UnivIS-Import:2019-08-15:Pub.2018.nat.dgeo.IGM.LP.apiran
Keywords: aggressive mimicry; convergent evolution; functional morphology; Late Jurassic; marine fishes; piranha-like dentition; Piranhamesodon; predation; Pycnodontiformes; Solnhofen Archipelago